A Rare Case of Intractable Laryngeal Sarcoidosis: A Case Report - Miyazaki, Masaru; Haraoka, Seiji; Sakata, Toshifumi; Yamano, Takafumi (International Journal of Practical Otolaryngology, 2020)
Laryngeal sarcoidosis is rare, and reports of recurrences after treatment are even rarer. A 49-year-old Japanese female patient visited our clinic with a 7-day history of dysphagia. Her medical history included sarcoidosis involving the cervical lymph nodes. Endoscopic examination revealed a diffusely swollen epiglottis and bilateral edema of the arytenoids. Corticosteroids and antibiotics were administered, but the laryngeal edema did not subside. Contrast-enhanced computed tomography imaging revealed bilateral low-density areas in the arytenoids. Therefore, we performed bilateral arytenoid biopsy under direct laryngoscopic guidance. The histopathology showed noncaseating epithelioid cell granulomas with moderate to severe chronic inflammatory infiltration; based on these findings, we diagnosed the patient as having laryngeal sarcoidosis. While the laryngeal edema did not recur for several months, arytenoid edema recurred 9 months after systemic steroid therapy. The patient's medical history of sarcoidosis of other organs as well as the presentation of edema of a supraglottic lesion and histopathological findings of noncaseating epithelioid cell granulomas led us to make the diagnosis of laryngeal sarcoidosis again. Laryngeal sarcoidosis is an important consideration in the differential diagnosis of laryngeal edema, as its therapy and clinical course are different from those for other diseases that present with laryngeal edema. A cautious follow-up of patients diagnosed as having laryngeal sarcoidosis is needed, because in rare cases, the laryngeal edema can become worse over time even after therapy.
Keywords: laryngeal sarcoidosis; laryngeal edema; epiglottitis; noncaseating epithelioid granuloma